Therapeutic mechanism of Pithecellobium clypearia Benth. on imiquimod-induced psoriasis revealed by tissue transcriptomics in mice - Xiyuan He; Yueting Mo; Peixin Shi; Yini Xu; Mingmei Zhou; Ting Zhang (PLoS ONE, 2025)
Background Psoriasis is an erythema papulosquamous dermatosis that cannot be cured at present. Pithecellobium clypearia Benth. belonging to the Leguminosae family and is clinically used as a treatment for gastroenteritis, acute tonsillitis, acute pharyngitis, and upper respiratory tract infections. Our previous studies have found that P. clypearia can improve imiquimod (IMQ)-induced psoriasis in mice and have revealed some differential metabolites and pathways using metabolomics methods. However, the underlying molecular mechanisms remain obscure. The purpose of this study is to investigate the therapeutic mechanism of the anti-psoriatic effects of P. clypearia using transcriptomics technology. Methods The psoriasis model was induced in male Balb/c mice by applying IMQ on their backs. To identify the differentially expressed genes (DEGs) among groups, RNA sequencing was employed. DEGs were analyzed using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and protein-protein interaction (PPI) network analysis. Furthermore, quantitative real-time PCR (qPCR) was employed for validation of these results. Results A total of 26 DEGs were identified, with several enriched pathways, including the MAPK signaling pathway, unfolded proteins response, hedgehog signaling pathways, NADH dehydrogenase activity, oxidative phosphorylation. Additionally, PPI network analysis revealed that gene Hspa1a was connected with Hspa1b , Bcl2 and GzmA , and Asns was related to Trib3 , Slc7a5 and Chac1 , and mt-Nd4l was correlated with mt-Nd5 and mt-Nd6 . The RNA-seq results were concordant with the qPCR results. Conclusions P. clypearia may ameliorate inflammation in psoriasis mice by modulating genes such as Hspa1a , Hspa1b , mt-Nd4l , mt-Nd5 , mt-Nd6 , Bcl2 , Asns , Trib3 , and associated pathways related to energy metabolism, cell growth, and apoptosis. Our study explored the underlying molecular mechanisms at the transcriptome level and provided a theoretical basis for further investigation into the efficacy of P. clypearia .